COVID-19 Testing and Vaccine Willingness: Cross-Sectional Survey in a Culturally Diverse Community in Sydney, Australia (Mary Ann Liebert, 2022)
Objective: The current study examined patterns in COVID-19 testing and vaccination intentions across multiple language groups in Greater Western Sydney, Australia. Methods: Participants completed a cross-sectional survey available from March 21 to July 9, 2021 in Sydney, Australia. Surveys were available in English or translated (11 languages). Participants could complete surveys independently or with support from bilingual staff. Logistic regression models using poststratification weighted frequencies identified factors associated with testing and vaccination intentions. Results: Most of the 708 participants (88%, n=622) were not born in Australia; 31% reported that they did not speak English well or at all (n=220); 70% had no tertiary qualifications (n=497); and 41% had inadequate health literacy (n=290). Half (53.0%) reported willingness to get a COVID-19 vaccine if recommended to them (n=375); 18% were unwilling (n=127), and the remainder unsure (29%, n=205). These proportions varied significantly by language group (p<0.001). Participants were more likely to be unwilling/hesitant if they were female (p=0.02) or did not use Australian commercial information sources (p=0.01). Concerns about side effects (30.4%, n=102) and safety (23.9%, n=80), were key reported barriers to vaccination. Most participants reported high testing intention (77.2%, n=546), with differences observed across language groups (p<0.001). The most frequently reported barrier to testing was concerns about infection at the clinic (26.1%) followed by concerns that testing was painful (25.3%). Conclusion: Different language groups have unique and specific needs to support uptake of COVID-19 testing and vaccination. Health services must work collaboratively with culturally and linguistically diverse communities to provide tailored support to encourage COVID-19 testing and vaccination.